2014
DOI: 10.3758/s13414-014-0675-6
|View full text |Cite
|
Sign up to set email alerts
|

Hide and seek: The theory of mind of visual concealment and search

Abstract: Researchers have investigated visual search behaviour for almost a century. During that time few studies have examined the cognitive processes involved in hiding items rather than finding them. To investigate this, we developed a paradigm that allowed participants to indicate where they would hide (or find) an item that was to be found (or hidden) by a friend or a foe. For friends, more than foes, participants selected (i) the popout item in the display and (ii) when the display was homogenous they selected ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(36 citation statements)
references
References 9 publications
4
30
2
Order By: Relevance
“…For example, Smilek, Weinheimer, Kwan, Reynolds, and Kingstone () have shown that participants asked to arrange search items to make search easy tend to centralize targets, group similar items, and arrange distractors in regular arrays. Similarly, Anderson, Foulsham, Nasiopoulos, Chapman, and Kingstone () report that individuals hiding an item for a friend (in contrast to hiding an item adversarially) tended to select a nearby, easy‐to‐reach location.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Smilek, Weinheimer, Kwan, Reynolds, and Kingstone () have shown that participants asked to arrange search items to make search easy tend to centralize targets, group similar items, and arrange distractors in regular arrays. Similarly, Anderson, Foulsham, Nasiopoulos, Chapman, and Kingstone () report that individuals hiding an item for a friend (in contrast to hiding an item adversarially) tended to select a nearby, easy‐to‐reach location.…”
Section: Discussionmentioning
confidence: 99%
“…The preference or avoidance for different places to hide objects is documented in Anderson et al (2014), Falk et al (2009), Legge et al (2012) and Talbot et al (2009). We asked ourselves whether the advent calendar creators show preference or avoid certain types of locations while placing Numbers 1, 2, .…”
Section: Test 5: Position Preferencesmentioning
confidence: 99%
“…This could be partly due to the differently shaped displays used in each study. For example, the interior squares of a 4 × 4 grid are avoided by hiders in a cooperative setting (Anderson et al, 2014) but not in a 5 × 5 grid (Falk et al, 2009) and generally preferred by these hiders in a certain L-shape display (Legge et al, 2012). Table 3 gives the correlation coefficients between pairs of the following tests: Test 1, distance between hiding places; Test 2, rates of spread with respect to 2 and 3 previous numbers; and Test 3, hit difference.…”
Section: Test 5: Position Preferencesmentioning
confidence: 99%
See 2 more Smart Citations